Benzimidazole derivatives act as dual urease inhibitor and anti-helicobacter pylori agent; synthesis, bioactivity, and molecular docking study. Issue 6 (19th March 2022) - Saeedian Moghadam, Ebrahim; Mohammed Al-Sadi, Abdullah; Ghafarzadegan, Reza; Talebi, Meysam; Amanlou, Massoud; Amini, Mohsen; Abdel-Jalil, Raid
Abstract: A series of benzimidazole derivatives 8a–h were synthesized in acceptable yield and characterized by spectroscopic methods such as 1 H-NMR, 13 C-NMR, MS, and Elemental analysis. In the urease inhibitory assay, all 8a–h showed higher urease inhibition activity (IC50 : 5.85–20.82 µM) in comparison to thiourea and hydroxyurea as standard (IC50 : 22 and 100 µM respectively). 8g exhibited the best activity with the IC50 value of 5.85 µM. The docking study represented a possible mode of interaction between 8g and the active site. To investigate the cytotoxicity of the synthesized compounds, an MTT assay was performed on two different cell lines which showed 8a–h have IC50 values higher than 50 µM on both tested cell lines. 8a–h were checked for antibacterial activity and the best activity was found by 8d against Helicobacter pylori with an inhibition zone of 20 mm even stronger than gentamicin with an inhibition zone of 18 mm. Graphical Abstract: UF0001